139 Single-question athlete self report measures in team sport athlete monitoring, and their relationship with training load: a systematic review and narrative synthesis. (3rd March 2020) - Duignan, Ciara; Doherty, Cailbhe; Caulfield, Brian; Blake, Catherine
Abstract : Background: Customised and sport specific athlete self-report measures (ASRM) of wellbeing are used and recommended commonly in injury and illness prevention, yet, there remains little uniformity in their use and design, and limited understanding of their relationship with training load (TL). Objective: To investigate the types of single-question ASRM used in team sport athlete monitoring practices and review their relationship with measures of TL. Design: Systematic review and narrative synthesis. Setting: Team sport (field and court) athletes >18 years old, at any competition level. Patients (or Participants): Twenty-two studies met the inclusion criteria and totalled 501 participants (soccer n=171; American football n=159; Australian football n=87; rugby sevens n=48; field hockey n=12; volleyball n=13; basketball n=11). Interventions (or assessment of risk factors): Studies were required to measure athlete well-being using a single-question self-report measure or measures, and investigate their relationship with a measure of modifiable TL over a minimum of 7 days. Main outcome measurements: ASRM design and description, and the existence and magnitude of a relationship between the ASRM and TL (correlation or regression). Results: Predominant single-item ASRM used were fatigue, sleep quality, muscle soreness, stress, and mood. Studies utilised general recommendations from the overtraining literature in the adoption of the ASRM, with heterogenous applications, scoring structures, and analyses, including use as both the independent and dependent variable with respect to TL. Both composite wellness scores and single-item measures displayed varying results from none to very large associations with measures of TL. Conclusions: Whilst the existence and magnitude of associations between single-item ASRM and measures of TL were varied, the associations found predominantly presented in the expected direction (i.e. a negative association). Implications of this review for practice are key considerations for users in the application and clinical utility of single-item ASRM in team sport athlete monitoring.